2019
DOI: 10.1016/j.cels.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

VISAGE Reveals a Targetable Mitotic Spindle Vulnerability in Cancer Cells

Abstract: Highlights d The MTH1 inhibitor TH588 synergizes with Plk1 inhibition to drive cancer cell death d VISAGE implicates the mitotic spindle, not MTH1, as the target of drug synergy d TH588 binds the colchicine binding site of b-tubulin blocking microtubule assembly d The cancer cell spindle is particularly vulnerable to Plk1 + microtubule inhibitors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 92 publications
9
34
1
Order By: Relevance
“…The two compounds have indistinguishable chemical-genetic interactions with genes involved in modulating the microtubule network (KIF2C and TACC3), both destabilize microtubules in cells and in vitro, and both show substantially reduced toxicity in cell lines expressing a rationally-designed mutant of tubulin (L240F TUBB mutant), in which the rigosertib binding site in tubulin is mutated. Importantly, the specificity of the L240F TUBB mutant for microtubule-destabilizing agents, which is disputed by Reddy and co-workers, was recently confirmed by an independent research group (Patterson et al, 2019). We conclude that rigosertib kills cancer cells by destabilizing microtubules, in agreement with our original findings.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The two compounds have indistinguishable chemical-genetic interactions with genes involved in modulating the microtubule network (KIF2C and TACC3), both destabilize microtubules in cells and in vitro, and both show substantially reduced toxicity in cell lines expressing a rationally-designed mutant of tubulin (L240F TUBB mutant), in which the rigosertib binding site in tubulin is mutated. Importantly, the specificity of the L240F TUBB mutant for microtubule-destabilizing agents, which is disputed by Reddy and co-workers, was recently confirmed by an independent research group (Patterson et al, 2019). We conclude that rigosertib kills cancer cells by destabilizing microtubules, in agreement with our original findings.…”
supporting
confidence: 90%
“…They found that TH588 synergizes with PLK1 inhibition in a manner that is independent of inhibition of MTH1, and through in-depth analysis found that TH588 destabilizes microtubules by binding in the same site as rigosertib. The L240F TUBB mutant indeed conferred resistance to TH588, but not to BI2536, which they used as a control (Patterson et al, 2019). Although this observation is published, Reddy and co-workers do not address the conflicting results, which are in support of our conclusions.…”
Section: Specificity Of Resistance Conferred By the L240f Tubb Mutantmentioning
confidence: 52%
See 1 more Smart Citation
“…Emerging evidence connect mitotic arrest with ROS. For instance, it has been shown that the level of ROS changes with cell cycle, where ROS is increased during mitosis and a mitotic arrest further enhances ROS levels [41]. Whether MTH1 directly alter ROS levels and plays a role during mitosis is still under debate.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a compound initially designed as MTH1 (Mut T homolog 1) inhibitor, TH588, was shown to dock into the colchicine-binding pocket [176]. By reducing microtubule plus end dynamics, this cyclopropyl analog affects tubulin polymerization, resulting in disruption of mitotic spindles, prolongation of mitosis and, eventually, apoptosis [176][177][178]. Preclinical studies show promising results for the use of TH588 as an anticancer drug [179,180].…”
Section: Colchicine Sitementioning
confidence: 99%